57Fe Mössbauer study of stoichiometric iron-based superconductor CaKFe4As4: a comparison to KFe2As2 and CaFe2As2. Issue 29 (13th October 2017) - Bud'ko, Sergey L.; Kong, Tai; Meier, William R.; Ma, Xiaoming; Canfield, Paul C.
Abstract: Fe Mössbauer spectra at different temperatures between and K were measured on an oriented mosaic of single crystals of . The data indicate that is a well formed compound with narrow spectral lines, no traces of other, Fe – containing, secondary phases in the spectra and no static magnetic order. There is no discernible feature at the superconducting transition temperature in any of the hyperfine parameters. The temperature dependence of the quadrupole splitting approximately follows the empirical ' law'. The hyperfine parameters of are compared with those for measured in this work, and the literature data for, and were found to be in between those for these two, ordered, 122 compounds, in agreement with the gross view of as a structural analog of and that has alternating Ca- and K-layers in the structure.